PERANAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (Pada Kabupaten dan Kota di Jawa Barat) - Lawe Anasta; Nengsih Nengsih (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
The purpose of this study to analyze the influence of local tax revenue and local retribution which is proxy by the pattern of budget target and the pattern of financial revenue which is measured by using its influence on local own source revenue at the local revenue office of district West Java in 2013-2017. And to find out how much the development of increasing Regional Original Income in West Java in 2013-2017. In this study using the theory of stewardship. Regional taxes and regional levies are sources of revenue from Regional Original Revenues. The research design used in this study is causal research with analysis using Multiple Regression to determine the development of Regional Tax and Regional Retribution for five years (2013 - 2017) in West Java. With statistical test units in the form of normality test, classic assumption test and hypothesis test. The dependent variable in this study is Regional Original Income, while the independent variable in this study is Regional Tax and Regional Retribution. Data quality testing shows that data is realized normally by testing The classic assumption is that there is a linear relationship between independent variables in the regression model. The greater the regional tax revenue and regional retribution, the greater the PAD received by the area. The greater the local revenue of west java it shows that the region is able to carry out fiscal decentralization and the dependence on the central government is reduced.The purpose of this study to analyze the influence of local tax revenue and local retribution which is proxy by the pattern of budget target and the pattern of financial revenue which is measured by using its influence on local own source revenue at the local revenue office of district West Java in 2013-2017. And to find out how much the development of increasing Regional Original Income in West Java in 2013-2017. In this study using the theory of stewardship. Regional taxes and regional levies are sources of revenue from Regional Original Revenues. The research design used in this study is causal research with analysis using Multiple Regression to determine the development of Regional Tax and Regional Retribution for five years (2013 - 2017) in West Java. With statistical test units in the form of normality test, classic assumption test and hypothesis test. The dependent variable in this study is Regional Original Income, while the independent variable in this study is Regional Tax and Regional Retribution. Data quality testing shows that data is realized normally by testing The classic assumption is that there is a linear relationship between independent variables in the regression model. The greater the regional tax revenue and regional retribution, the greater the PAD received by the area. The greater the local revenue of west java it shows that the region is able to carry out fiscal decentralization and the dependence on the central government is reduced.